Anxiety in Programming Course of University Students: Does It Affect Students’ Performance? - Putri, Tansa Trisna Astono; Rahmadani, Reni; Hasan, Hanapi (Cattleya Darmaya Fortuna, 2024)
In the context of programming, anxiety typically refers to the feeling of unease or worry that can arise when working on software development tasks or projects. It is a psychological and emotional response to the challenges and uncertainties that programmers often face. In this study, undergraduate students of Computer and Electricical Engineering often work under strict deadlines and face pressure to deliver high-quality code. In this study, undergraduate students often work under strict deadlines and face pressure to deliver high-quality code. This can lead to anxiety as they strive to meet expectations and complete tasks on time. Programming involves solving complex problems, and sometimes the solutions are not immediately apparent. This can create anxiety as programmers grapple with uncertainty and the fear of making mistakes for undergraduate students. The purpose of this quantitative study was to look into anxiety as the root cause of students' poor programming performance. The results of this study will aid in providing the most effective approach for instructing and learning programming courses in order to generate competent programmers for use in business settings and higher education. Data for this quantitative study were gathered via the questionnaire. The study found that the degree of unfavourable beliefs about control in computing scenarios and the low level of computing self-efficacy found in this study indicate that computer programming course designers must come up with ways to boost students' confidence and motivation.